Preparation of PEO coating on Ti6Al4V in different electrolytes and evaluation of its properties. (2nd June 2016) - Khanmohammadi, H.; Allahkaram, S. R.; Towhidi, N.; Rashidfarokhi, A. M.
Abstract : The aim of this work is to discuss the effect of different amounts of NaF in electrolyte on structure, corrosion resistance and wear behaviour of the prepared ceramic coatings on Ti6Al4V alloy by plasma electrolytic oxidation (PEO) technique. PEO process was carried out under constant current of 2 A, frequency of 1 kHz, anodic duty cycle of 45% and cathodic duty cycle of 25% using a pulse bipolar power supply. TiO2 based coatings were prepared from three aluminate base electrolytes containing various amount of NaF (0.75, 1.5 and 2.25 g L −1 ). Phase composition, surface morphology and thickness of the resultant coatings were examined by means of X-ray diffraction and field emission scanning electron microscopy. Results indicated that solution composition and process time have a great effect on thickness and surface porosity of the coatings. Corrosion resistance and wear properties of the coatings were in a good accordance with structural properties.